Degradative Capacity of Two Strains of Rhodonia placenta: From Phenotype to Genotype - Kölle, Martina; Horta, Maria Augusta Crivelente; Nowrousian, Minou; Ohm, Robin A.; Benz, J. Philipp; Pilgård, Annica (Frontiers in Microbiology, 2020)
Brown rot fungi, such as Rhodonia placenta (previously Postia placenta), occur naturally in northern coniferous forest ecosystems and are known to be the most destructive group of decay fungi, degrading wood more effectively than other wood-degrading organisms. It has been shown that brown rot fungi not only rely on enzymatic degradation of lignocellulose, but also use low molecular weight oxidative agents in a non-enzymatic degradation step prior to enzymatic degradation. R. placenta is used in standardized decay tests in both Europe and North America. However, two different strains are employed (FPRL280 and MAD-698, respectively) for which differences in colonization-rate, mass loss, as well as in gene expression have been observed, limiting the comparability of results. To elucidate the divergence between both strains, we investigated the phenotypes in more detail and compared their genomes. Significant phenotypic differences were found between the two strains, and no fusion was possible. MAD-698 degraded scots pine more aggressively, had a more constant growth rate and produced mycelia faster than FPRL280. After sequencing the genome of FPRL280 and comparing it with the published MAD-698 genome we found 660,566 SNPs, resulting in 98.4 % genome identity. Specific analysis of the carbohydrate-active enzymes, encoded by the genome (CAZome) identified differences in many families related to plant biomass degradation, including SNPs, indels, gaps or insertions within structural domains. Four genes belonging to the AA3_2 family could not be found in or amplified from FPRL280 gDNA, suggesting the absence of these genes. Differences in other CAZy encoding genes that could potentially affect the lignocellulolytic activity of the strains were also predicted by comparison of genome assemblies (e.g. GH2, GH3, GH5, GH10, GH16, GH78, GT2, GT15 and CBM13). Overall, these mutations help to explain the phenotypic differences observed between both strains as they could interfere with the enzymatic activities, substrate binding ability or protein folding. The investigation of the molecular reasons that make these two strains distinct contributes to the understanding of the development of this important brown rot reference species and will help to put the data obtained from standardized decay tests across the globe into a better biological context.